1973
DOI: 10.1070/pu1973v015n04abeh005027
|View full text |Cite
|
Sign up to set email alerts
|

NIKOLAĬ VASIL'EVICH FEDORENKO (Obituary)

Abstract: In a previous communication to the Society the occurrence of wireless echo doublets was described and was provisionally attributed to the influence of the earth's magnetic field on the dispersive properties of the ionosphere. A more extended study of the subject, which has included an experimental determination of the polarizations of the doublet-components, has confirmed this hypothesis. In South-east England, for ionospheric reflection at vertical incidence, the echo-component of lesser delay is, in general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The more strongly first-order character of the phase change in PbTiO 3 makes equation (3) applicable only in the monophasic tetragonal state below T 0 [20], as seen more clearly in the inset of the figure. However, extrapolation of the data in the linear range at 730 K T 750 K to ( C P /T ) −2 = 0 gives T * = (764 ± 2) K in agreement with the relation [19]…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The more strongly first-order character of the phase change in PbTiO 3 makes equation (3) applicable only in the monophasic tetragonal state below T 0 [20], as seen more clearly in the inset of the figure. However, extrapolation of the data in the linear range at 730 K T 750 K to ( C P /T ) −2 = 0 gives T * = (764 ± 2) K in agreement with the relation [19]…”
Section: Resultssupporting
confidence: 81%
“…Figure 3 shows the plot constructed from the C P data and it was found that equation (3) holds well (R 2 = 0.999) over the interval τ = 0.013-0.049. This interval of τ is somewhat smaller than expected as compared with other perovskite crystals with displacive transitions lying closer to a mean-field tricritical point [19]. The more strongly first-order character of the phase change in PbTiO 3 makes equation (3) applicable only in the monophasic tetragonal state below T 0 [20], as seen more clearly in the inset of the figure.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It is difficult to continuously vary the relevant thermodynamic parameters with the accuracy needed to arrive precisely at the tricritical points (9). Microcrystalline features of the sample, such as chemical heterogeneity and/or lattice imperfections, may also depend on composition, and can exert a considerable influence on the nature of the transition (10). Perhaps for these reasons, there are significant discrepancies in the reported compositions at which the tricritical points occur.…”
Section: Introductionmentioning
confidence: 99%
“…In the mean-field theory, a change in the order of the transition is predicted to occur subject to the influence of an external parameter only if higher-order elastic terms, electrostrictive terms, or both are included in the Landau potential [26], or alternatively, if the lower-order terms adopt sufficiently renormalized values with respect to a variation in chemical composition in mixed crystals [27]. The applicability of the Landau theory to transitions near mean-field TCPs in solids both with and without impurities has been discussed in general terms by several authors [28,29].…”
Section: Resultsmentioning
confidence: 99%